Sport i wyścigi konne w mniej znanych i zapomnianych tekstach z 2. połowy XIX i początków XX wieku. Wstępne rozpoznania - Kochanowski, Marek (Poznańskie Studia Polonistyczne. Seria Literacka, 2024)
The article presents various approaches to the subject of sport in forgotten literary works from the second half of the 19th century and early 20th century by Konstanty Gaszyński, Klemens Junosza, Kazimierz Laskowski and Lucjan Rydel. The first two pieces show horse racing as a threat to the tradition of the landed gentry caused by gambling, fashions and foreign influences. Rydel’s contrasting text avoids an ironic tone, the poet describes the Olympic Games as a culture-creating event, as the founding myth of the Mediterranean civilization. The forgotten texts show sport in the literature of the turn of the 20th century and indicate that it played an important role in the discussion on the mechanisms of tradition and cultural heritage.